2016
DOI: 10.1371/journal.pone.0150803
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Regulating Insulin Response to Intragastric Glucose in Lean and Non-Diabetic Obese Subjects: A Randomized, Double-Blind, Parallel-Group Trial

Abstract: Background/ObjectivesThe changes in blood glucose concentrations that result from an oral glucose challenge are dependent on the rate of gastric emptying, the rate of glucose absorption and the rate of insulin-driven metabolism that include the incretins, glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide-1 (GLP-1). The rate of insulin-driven metabolism is clearly altered in obese subjects, but it is controversial which of these factors is predominant. We aimed to quantify gastric emptyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…Test solutions were labeled with 50 mg of 13 C-sodium acetate [15]. As described in detail previously [10], at fixed time intervals after administration of the test solution (15, 30, 45, 60, 75, 90, 105, 180, 210 and 240 min), end-expiratory breath samples were taken into a 100 mL foil bag. The 13 C-exhalation was determined by non-dispersive infrared spectroscopy using an isotope ratio mass spectrophotometer (IRIS ® ; Wagner Analysen Technik, Bremen, Germany), and expressed as the relative difference (δ ‰) from the universal reference standard (carbon from Pee Dee Belemnite limestone).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Test solutions were labeled with 50 mg of 13 C-sodium acetate [15]. As described in detail previously [10], at fixed time intervals after administration of the test solution (15, 30, 45, 60, 75, 90, 105, 180, 210 and 240 min), end-expiratory breath samples were taken into a 100 mL foil bag. The 13 C-exhalation was determined by non-dispersive infrared spectroscopy using an isotope ratio mass spectrophotometer (IRIS ® ; Wagner Analysen Technik, Bremen, Germany), and expressed as the relative difference (δ ‰) from the universal reference standard (carbon from Pee Dee Belemnite limestone).…”
Section: Methodsmentioning
confidence: 99%
“…The 13 C-exhalation was determined by non-dispersive infrared spectroscopy using an isotope ratio mass spectrophotometer (IRIS ® ; Wagner Analysen Technik, Bremen, Germany), and expressed as the relative difference (δ ‰) from the universal reference standard (carbon from Pee Dee Belemnite limestone). The calculation of percent of administered dose of 13 C excreted per hour (%dose/h) has previously been described in detail [10]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin in overweight patients does not only suppress lipolysis but also slows down fat absorbtion. Unfortunately, insulin makes it more effectively when the body weight is higher, which was reported by a research team from Basel University Clinic (156,159). It was shown that glucose load in patients with body mass index ≥ 30 kg/m 2 increases the level of insulin more than when BMI ≤ 25 kg/m 2 .…”
Section: K E T O G E N I C D I E T F O R R E D U C T I O N O F W E I mentioning
confidence: 98%
“…Horowitz et al (17) showed that gastric emptying accounts for one-third of the variance in the postprandial glucose kinetics of healthy individuals. Further studies suggest that the dynamics of gastric emptying is altered in obese patients (18,24,28) affecting glucose absorption and postprandial glycemia (16,27,32,40).…”
mentioning
confidence: 99%